Meningkatkan Keaktifan Belajar Siswa Melalui Model Game-Based Learning Berdiferensiasi Kahoot di Madrasah Ibtidaiyah Swasta Nurunnajah Olak Kemang Kota Jambi - M. Syarfrengki; Mahluddin Mahluddin (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This study was carried out to boost the learning enthusiasm of fifth-grade students at Madrasah Ibtidaiyah Swasta Nurun Najah Olak Kemang, Kota Jambi. The method used was a Game-Based Learning model that was adjusted to suit the students’ needs, using the Kahoot app. The research followed a Classroom Action Research approach with two cycles, and each cycle included steps like planning, doing the activity, observing, and reflecting. To collect the data, the researcher used observation sheets, interviews, and documentation. The results showed a noticeable increase in how engaged the students were. In the beginning (pre-cycle), the average engagement was only 55.90%, and most students were not very active. After the first cycle, it went up to 61.45%, and by the second cycle, it jumped to 82.81%, with most students becoming active or even very active. Using Kahoot helped create a fun and interactive learning atmosphere, which made the students more eager to participate. So, using a game-based approach like this with Kahoot can be a good option to make elementary students more involved in learning.